Prevalence of undiagnosed metabolic syndrome using three different definitions and identifying associated risk factors among apparently healthy adults in Karachi, Pakistan: a cross-sectional survey in the year 2022 - Syed Omair Adil; Kamarul Imran Musa; Fareed Uddin; Asima Khan; Irfanullah Khan; Areebah Shakeel; Kashif Shafique; Md Asiful Islam (Archives of Public Health, 2024)
Abstract Objective To determine the prevalence and associated risk factors of undiagnosed metabolic syndrome (MetS) using three different definitions among apparently healthy adults of Karachi, Pakistan. Methods This community-based cross-sectional survey was conducted in Karachi, Pakistan, from January 2022 to August 2022. A total of 1065 healthy individuals aged 25–80 years of any gender were consecutively included. MetS was assessed using the National Cholesterol Education Program for Adult Treatment Panel (NCEP-ATP) III guidelines, International Diabetes Federation (IDF), and modified NCEP-ATP III. Results The prevalence of MetS was highest with the modified NCEP-ATP III definition at 33.9% (95% CI: 31–36), followed by the IDF definition at 32.2% (95% CI: 29–35). In contrast, the prevalence was lower at 22.4% (95% CI: 19–25) when using the NCEP ATP III definition. The risk of MetS significantly increases with higher BMI, as defined by the IDF criteria (adjusted OR [ORadj] 1.13, 95% CI 1.09–2.43), NCEP-ATP III criteria (ORadj 1.15, 95% CI 1.11–1.19), and modified NCEP-ATP III criteria (ORadj 1.16, 95% CI 1.12–1.20). Current smokers had significantly higher odds of MetS according to the IDF (ORadj 2.72, 95% CI 1.84–4.03), NCEP-ATP III (ORadj 3.93, 95% CI 2.55–6.06), and modified NCEP-ATP III (ORadj 0.62, 95% CI 0.43–0.88). Areca nut use was associated with higher odds of MetS according to both IDF (ORadj 1.71, 95% CI 1.19–2.47) and modified NCEP-ATP III criteria (ORadj 1.58, 95% CI 1.10–2.72). Furthermore, low physical activity had significantly higher odds of MetS according to the NCEP-ATP III (ORadj 1.36, 95% CI 1.01–1.84) and modified NCEP-ATP III criteria (ORadj 1.56, 95% CI 1.08–2.26). Conclusion One-third of the healthy individuals were diagnosed with MetS based on IDF, NCEP-ATP III, and modified NCEP-ATP III criteria. A higher BMI, current smoking, areca nut use, and low physical activity were significant factors.